2022
DOI: 10.1128/spectrum.01952-21
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole Population Pharmacokinetics after Fosfluconazole Administration and Dosing Optimization in Extremely Low-Birth-Weight Infants

Abstract: Invasive fungal infection is an important cause of mortality and morbidity in very preterm or very-low-birth-weight infants. In order to limit the risk of invasive fungal infections in this population, the administration of fluconazole is generally recommended for extremely low-birth-weight infants admitted to a neonatal intensive care unit with a Candida species colonization prevalence rate of >10%, under the guidelines of the Infectious Diseases Society of America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…PK analysis of antimicrobial agents using population PK has been progressing in the Japanese pediatric field (Table 2). 32,[41][42][43][44][45][46][47][48][49] Shoji et al reported on the population PK analysis of meropenem in critically ill patients in the pediatric intensive care unit. 45 In this study, the authors reported that a longer time above MIC might result in a shorter time to resolution of fever and higher efficacy, and that patients with more severe inflammation (patients presenting with one or more systemic inflammatory response syndrome criteria) are more likely to have higher clearance of meropenem and may not achieve adequate time above MIC with standard doses.…”
Section: Application Of Population Pharmacokinetics In Research For C...mentioning
confidence: 99%
See 1 more Smart Citation
“…PK analysis of antimicrobial agents using population PK has been progressing in the Japanese pediatric field (Table 2). 32,[41][42][43][44][45][46][47][48][49] Shoji et al reported on the population PK analysis of meropenem in critically ill patients in the pediatric intensive care unit. 45 In this study, the authors reported that a longer time above MIC might result in a shorter time to resolution of fever and higher efficacy, and that patients with more severe inflammation (patients presenting with one or more systemic inflammatory response syndrome criteria) are more likely to have higher clearance of meropenem and may not achieve adequate time above MIC with standard doses.…”
Section: Application Of Population Pharmacokinetics In Research For C...mentioning
confidence: 99%
“…Furthermore, we conducted population PK analysis of fosfluconazole in extremely low birth weight infants and explored the optimal dosing in this population. 41 Recently, the information obtained by physiologically based pharmacokinetic modeling and population PK analysis information from real-world data are being utilized and some of them are reflected in the package inserts globally. [50][51][52][53] We have started collaboration with a pharmaceutical company for PK analysis utilizing academic clinical trial data and are currently discussing with Japanese regulators and industry representatives how we can utilize the real-world PK/PD information for regulatory purposes in Japan.…”
Section: Application Of Population Pharmacokinetics In Research For C...mentioning
confidence: 99%